Bacterial microleakage of temporary filling materials, IRM and Cavit An in vitro study - Pattugalan, Cheremyn M.
One of the objectives of root canal therapy is to seal the root canal system effectively to prevent ingress of food, debris and bacteria. Penetration of bacteria into the root canal and to the periapical area causes root canal treatment to fail. Cleaning, shaping, and obturating the root canal requires multiple appointments hence interim restorations are used to seal the access preparation in between appointments. Intermediate restorative material (IRM) and Cavit are temporary filling materials used at the UP College of Dentistry. This study aimed to see if there was a difference in the sealing efficiency of IRM and Cavit. Standard endodontic access preparations were done on 50 single rooted teeth. Twenty-five teeth were filled with IRM and the other 25 were filled with Cavit. Two days after, 10 teeth from each group were thermocycled. Color changes and turbidity in the upper chambers of the model systems, which were indicators of microleakage, were observed for 19 days. Ueakage was first observed during the second week. On the last day of observation, 19 out of 25 from the Cavit group leaked (13 out of 15 from the thermocycled group and 6 out of 10 from the non-thermocycled group). While 17 out of 25 leaked from the IRM group (11 out of 15 from the thermocycled group and 6 out of 10 from the non-thermocycled group). The Fisher Exact Test was used to see if there was a correlation between the kind of filling and microleakage as well as thermocycling and microleakage. Results show that there was no correlation between the kind of filling and microleakage, and thermocycling and microleakage. The Kruskal-Wallis (KW) One-Way Analysis of Variance by Ranks was used to see if there is a significant difference in the number of days wherein leakage was observed in the upper chambers. A KW result of 9.323854 deviates from the mean KW value of 7.82, meaning, there is a significant difference between the length of time the model systems were immersed in the bacterial medium and microleakage. The researchers can therefore conclude that IRM and Cavit are efficient, temporary filling materials in terms of sealing, but only for a certain period of time.